PENGARUH PEMBERIAN BAHAN HUMAT DARI EKSTRAK BATUBARA MUDA (Subbituminus) DAN PUPUK P TERHADAP SIFAT KIMIA ULTISOL SERTA PRODUKSI TANAMAN JAGUNG (Zea mays L.) - Herviyanti Herviyanti; Fachri Ahmad; Riza Sofiyani; Darmawan Darmawan; Gusnidar Gusnidar; Amrizal Saidi (Jurnal Solum, 2012)
The purpose of this research is to study interaction of humic substances extracted from subbituminus coal with P fertilizer on the chemical properties of Ultisol and crop production of corn (Zea mays L.). The experiment was designed in completely randomized design having 2 factors (4 x 4) with 3 replications. The first factor was dose of humic substances (A) which consists of 4 levels (A1 = 0 ppm, A2 = 400 ppm, A3 = 800 ppm, and A4 = 1200 ppm). The second factor was level of fertilizer P (B) (B1 = 100% recommendation, B2 = 75% recommendation, B3 = 50% recommendation, and B4 = 25%). The result showed that : 1) There is no interaction between humic substances and P fertilizer on the chemical nature of Ultisol and crop production of corn (Zea mays L.) 2) Use of humic substance for 800 ppm with some level of P fertilizer could improve some chemical properties of Ultisol such as decreased in content of Al-exch by 0,38 me/100 g soil, increased in P-available by 22,16 ppm, CEC by 8,42 me/100 g soil and P nutrient by 0,10 %, as well as corn yield by 25,67 g/pot compared to soil without humic substances 3) The use of SP-36 for 50 % with some level of humic substances increased in plant height by 26,58 cm, P nutrient by 0,11 %, and the use of 75 % SP-36 increased corn yield by 5,84 g/pot compared to 25% of P recommended.Keywords : humic subtances, subbituminus coal, P fertilizer.